2016
DOI: 10.1080/14786435.2016.1224945
|View full text |Cite
|
Sign up to set email alerts
|

The effect of size on the strength of FCC metals at elevated temperatures: annealed copper

Abstract: As the length scale of sample dimensions is reduced to the micron and sub-micron scales, the strength of various materials has been observed to increase with decreasing size, a fact commonly referred to as the ‘sample size effect’. In this work, the influence of temperature on the sample size effect in copper is investigated using in situ microcompression testing at 25, 200 and 400 °C in the SEM on vacuum-annealed copper structures, and the resulting deformed structures were analysed using X-ray μLaue diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In Figure 4 , we could see images of micro-pillars with different taper angles after compression in a load-controlled regime. The plastic flow in case of micro-pillars with smaller taper angles (≤7°) was localized in the form of small-scale shear bands that were similar to those observed in the sample MoBC AM ; however, in this case, the coating was composed of nanosized grains, and, thus, the shearing could be explained by grain boundary sliding mechanism that is typical for polycrystalline metallic micro-pillars [ 21 , 22 ]. On the other hand, for higher taper angles in the range between 7° and 12°, the excessive stress concentrations close to the top of micro-pillars resulted in a higher probability of large-scale localized specimen failure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Figure 4 , we could see images of micro-pillars with different taper angles after compression in a load-controlled regime. The plastic flow in case of micro-pillars with smaller taper angles (≤7°) was localized in the form of small-scale shear bands that were similar to those observed in the sample MoBC AM ; however, in this case, the coating was composed of nanosized grains, and, thus, the shearing could be explained by grain boundary sliding mechanism that is typical for polycrystalline metallic micro-pillars [ 21 , 22 ]. On the other hand, for higher taper angles in the range between 7° and 12°, the excessive stress concentrations close to the top of micro-pillars resulted in a higher probability of large-scale localized specimen failure.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 3 b shows an image of the corresponding micro-pillar after deformation with the flat punch indenter. We could see that the deformation led to the formation of several shear bands close to the top of the pillar resembling slip traces caused by grain boundary sliding in metals [ 21 , 22 ], albeit, in this case, the coatings posed amorphous microstructure. The sliding mechanism could be explained by the movement of the so-called Somigliana dislocations observed in metallic glasses [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such observations involving extremely small dimensionally-dependent mechanical property measurements have followed a pioneering report by Brenner [6] of greatly-enhanced strength levels being achieved for smaller diameter "whisker" materials. This was later established for nano-grained steel wire [7], micro-pillar α-iron [8], and copper [9] materials. The strength levels have been attributed either to higher applied stresses being needed to nucleate individual dislocations within a dislocation-free environment or because of the need for internal stress concentrations to be produced by small dislocation pile-ups [10][11][12], for example, as established in the description of higher micro-hardness levels reached for nano-grained nickel material [13].…”
Section: Introductionmentioning
confidence: 98%
“…Laue microdiffraction has been used before on small-scale samples: Barabash et al showed that (i) the continuous streaking of Laue diffraction peaks can be related to internal strain gradients and (ii) discontinuous streaking happens in the presence of dislocation walls forming geometrically necessary boundaries [16]. Since then, Laue microdiffraction has been established as a powerful technique in the study of mechanisms that govern plastic deformation at the micro scale [17][18][19][20][21]. For instance, Maaß et al [18] performed in situ compression tests on ion-milled Au micropillars.…”
Section: Introductionmentioning
confidence: 99%